Political Life Writing in the Pacific. Reflections on Practice - Corbett, Jack (ANU Press, 2015)
This book aims to reflect on the experiential side of writing political lives in the Pacific region. The collection touches on aspects of the life writing art that are particularly pertinent to political figures: public perception and ideology; identifying important political successes and policy initiatives; grappling with issues like corruption and age-old political science questions about leadership and 'dirty hands'. These are general themes but they take on a particular significance in the Pacific context and so the contributions explore these themes in relation to patterns of colonisation and the memory of independence; issues elliptically captured by terms like 'culture' and 'tradition'; the nature of 'self' presented in Pacific life writing; and the tendency for many of these texts to be written by 'outsiders', or at least the increasingly contested nature of what that term means.